Causes and consequences of pedestrian injuries - victims of road accidents - Goniewicz, Krzysztof; Goniewicz, Mariusz; Rzońca, Patryk; Pawłowski, Witold; Czerski, Robert (Journal of Education, Health and Sport, 2017)
Road accidents are a serious problem of the modern world. They are one of the main causes of all injuries, which represent the third leading cause of death in the world. The research presents the problem of the road accidents, with particular emphasis on road accidents involving pedestrians and characterize the most common injuries are suffered by pedestrians in the road accidents. The type and extent of pedestrian injuries among the victims of road accidents mainly depends on four factors: the speed of the vehicle, construction vehicle, the braking maneuver carried out by driving a vehicle and age of the victim. The most important factor affecting the consequences of accidents on the victims is the vehicle speed at the time of collision. In adults, injuries occur most frequently located within the limbs.